In vitro electrically controlled amoxicillin release from 3D-printed chitosan/bismuth ferrite scaffolds - ÇALIKOĞLU KOYUNCU, AYŞE CEREN (My University, 2023)
The goal of this study was to design and fabricate a 3D-printed wound dressing using chitosan as a bioink, with the ability to release the antibiotic drug amoxicillin (AMX) in response to mild electrical stimulation. This was achieved through the incorporation of bismuth ferrite (BFO) nanoparticles, which have both magnetic and ferroelectric properties. The chitosan-based scaffolds containing various concentrations of BFO were analyzed using Fourier transform infrared spectroscopy, and the release of AMX from the scaffolds was evaluated in vitro under electrical stimulation. The results demonstrated that the scaffolds had a suitable structure for drug loading and release, and the release of AMX was successfully controlled by the applied electrical stimulus. The maximum tensile strength (4.97 ± 0.34 MPa) was observed at the ratio of 6% CHT/0.025% BFO scaffolds and the scaffold with 6% CHT/0.075% BFO had the maximum cell viability of (~130%) at 168 h incubation time. This study highlights the potential of BFO to deliver therapeutic drugs from a 3D-printed chitosan scaffold in a controlled manner.
Keywords: Metalurji ve Malzeme Mühendisliği; Malzeme Bilimi ve Mühendisliği; Mühendislik ve Teknoloji; Metallurgical and Materials Engineering; Material science and engineering; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Malzeme Bilimi; METALURJİ VE METALURJİ MÜHENDİSLİĞİ; Engineering, Computing & Technology (ENG); MATERIALS SCIENCE; METALLURGY & METALLURGICAL ENGINEERING; Amoxicillin; Bismuth ferrite; Chitosan; Controlled drug delivery; Scaffold; 3D printing